Self reported health conditions and nutritional status of elderly people living in old age homes of Lalitpur District. - Dangol, Shreejana (2020)
ABSTRACT: BACKGROUND: Elderly population is defined as the population of aged 60 and over. The population of older adults, 60 years and above, in Nepal has increased from 1.5 million to 2.2 million in 2011. Self-assessed health status is a measure of how an individual perceives his or her health-rating it as excellent, very good, good, fair, or poor. World-wide, the elderly population is increasing, and so is the prevalence of malnutrition. Despite significant medical advances, undernutrition remains a significant and highly prevalent public health problem of developed countries. The nutritional status of elderly living in old age homes is found to be slightly bad than elderly living at their own homes. OBJECTIVES: To assess health conditions and the nutritional status of Elderly people living in old age homes of Lalitpur. METHODOLOGY: This study is a cross-sectional study conducted among 197 elderly people residing in old age homes of Lalitpur district. Respondents were interviewed with self-rating health check list and screening tool Mini Nutritional Assessment. Data were exported to and analysed using SPSS11.5. Descriptive, bivariate (chi-square test and Kruskal Wallis test) and multivariate analysis were applied for assessing the association between the variables at 95% confidence interval (CI). RESULTS: In this study, 49.7% respondents self-rated their health as moderate or fair. Among total respondents, 58.4% were nourished, 37.6% were at risk of malnourishment and 4.1% were malnourished. Variables such as marital status (OR=6.038, p=0.049), smoking (OR=9.639, p=0.008), alcohol consumption (OR=7.083, p=0.029) and number of meals a day were found to be the factors to affect self-reporting of health conditions. Similarly, marital status (AOR=4.488, p=0.034), educational status (AOR=4.541, p=0.033) and presence of chronic illness (AOR=6.107, p=0.013) were found to be factors associated with nutritional status of elderly people. CONCLUSION: Presence of co-morbidities and lifestyle highly affect in self-rating of health and nutritional status. The prevalence of at-risk of malnutrition was high among elderly people. Key Words: Self-reported health condition, nutritional status, elderly people, old age homes, Mini Nutritional assessment.